2018
DOI: 10.23860/jmle-2018-10-03-07
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Media in the College Classroom: A Longitudinal Critical Media Literacy Intervention

Abstract: While many studies have addressed the impact of media literacy interventions on knowledge of specific topic areas, fewer have explored improvements in media literacy skills as outcome measures. This study analyzed the impact of a media literacy intervention on participants' critical thinking skills and understanding of media literacy principles by addressing the topics of body image and media representations of gender and race. A two-group, longitudinal experimental design was implemented using college-aged st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Research on media awareness of digital literacy can be found in Fitryarini (2014); Bulger & Davison (2018); Akcayoglu & Daggol (2019); Solmaz (2017); and Bergstrom, Flynn, & Craig (2018). These studies have seen media awareness from a number of sides.…”
Section: Media Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on media awareness of digital literacy can be found in Fitryarini (2014); Bulger & Davison (2018); Akcayoglu & Daggol (2019); Solmaz (2017); and Bergstrom, Flynn, & Craig (2018). These studies have seen media awareness from a number of sides.…”
Section: Media Awarenessmentioning
confidence: 99%
“…These foregoing studies show that there is a threat on media awareness if teachers are not able to secure media awareness in learning. Bergstrom et al (2018), on the other hand, see the positive side: in the control and experiment group design, the experiment group receiving the intervention of media literacy show awareness in the use of media literacy.…”
Section: Media Awarenessmentioning
confidence: 99%
“…One strand of news and media literacy research focuses on evaluating courses, modules, interventions, or curricula to see how these efforts improve literacy, which is usually measured as a specific type of knowledge, attitude, or skill that is often directly related to the effort. 21 Another strand of research looks at the relationship between news and media literacy and a range of outcomes related to critical news consumption, such as perceptions of news and information accuracy, bias, credibility, and hostility. 22 For example, research suggests that news literacy efforts can improve credibility perceptions of news and can make people more skeptical of biased, false, or misleading information and conspiracy theories even when this content aligns with their worldviews.…”
Section: How Can Research Inform News Literacy Efforts?mentioning
confidence: 99%
“…CRML studies focus on the role media takes in perpetuating stereotypes and ideologies of marginalized and underrepresented people and institutional systems of oppression (Baynes, 2002;Bergstrom et al, 2018;Dixon, 2008;Entman & Gross, 2008;Joanou, 2017;King 2017;Yosso, 2002). While still 4 focusing on analysis, CRML moves beyond the development of informed citizens and calls for further analysis of the lived experiences of marginalized populations.…”
Section: A Focus On Racementioning
confidence: 99%